ANALISIS TARIKAN PERGERAKAN PENGUNJUNG PASAR BINA USAHA DI KOTA MEULABOH - Meidia Refiyanni; Azwanda Azwanda; Andrisman Satria (Universitas Teuku Umar, 2018)
Prior to expansion of area, West Aceh had an area of 10,097.04 km2 or 1,010,466 ha after expansion of the West Aceh area to 2,927.95 km2, consisting of 12 sub-districts and 322 villages. The city of Meulaboh is located in Johan Pahlawan Subdistrict, one of the sub-districts of Meulaboh City that has a shopping center, the Business Development Market. Pasar Bina Usaha is the best-selling shopping center on the southwest coast, with congestion due to increasing community activity. This increase in activity is caused by the large number of movements of houses - markets - houses that affect the existing transport system. Against this background, it is necessary to examine the trait of the movement of the community from the home market house with the attraction model of the market visitors. Based on the analysis of the dominant factors influencing the attractiveness of the business market visitors, the number of family members (X1), the number of motorcycles (X3), the number of marketers (X9), the transport costs (X11), the number of marketers per day (X12) travel time (X15) and age (X16). Weekdays are dominated by the number of family members (X1), the number of motorcycles (X3), the distance of the market houses (X8), the number of marketers (X9), the number of marketers per day (X12), the purchase cost (X14 ) and travel time (X15), age (X16)